SOSIO-TEOLOGIS: MEMAHAMI DUALITAS PERSPEKTIF PLURALISME AGAMA DI INDONESIA - Noor Rachmat (Harmoni, 2012)
This paper is backgrounded by the importance of concept on plurality. Plurality is a need for inter-understanding other religion, openeness, tolerance and cooperation. The ultimate objective is cooperation in differences. The method used in this study is library research, discourse technique and hermeunetique in religious texts and other literature. Study shows sociological pluralism should be developed, based on two matters. The first, pluralism is a social attitude and social action of a religious community wether in one or more religions. The second, pluralism in social process which is related with religious dialogue. In the Islamic teaching of `Wahdat al-Adyan`, the principle of pluralism has been existing in classical teaching of Islam, e.g. in an Al Quran verse states that God creates differences on almost all intentionally, it must look as a natural law and not need more argumentation.